Study guides

☆☆

Q: What is 4b minus 2c?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals".

Well I got this: 2c+7=9+6-7c+2c 2c+7=15-9c 11c+7=15 (add 9c) 11c=8 ( Subtract 7) 11---11 ( Divide 11) C=0.72

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

Related questions

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b

8b - 4b = 4b

2c

-2c

What is sentencing for a 2C:28-4B

c-2b

b^3 - 25b^2 - 4b + 100 = 0 b = 25 or b = -2

Numerically, if the question looks like this:--(3a + 7b) - 8a - 4b + 2Then the answer is this:--3a - 7b - 8a - 4b + 2= -11a -11b + 2

In its most simplified form: = 12abc + 8bc - 20ab = 4b(3ac + 2c - 5a) = 4b[(c + 5/3)(3a + 2) - 10/3]

3a + 5b - 6a - 9b = -3a - 4b

That depends what the values of k and b are.

People also asked

Featured Questions